2014
DOI: 10.3389/fnbeh.2014.00113
|View full text |Cite
|
Sign up to set email alerts
|

The effects of valproic acid on appetitive and aversive instrumental learning in adult rats

Abstract: Antiepileptic medications are the frontline treatment for seizure conditions. However, these medications are not without cognitive side effects. Previously, our laboratory reported learning deficits in phenytoin and carbamazepine-treated rats. In the experiment reported here, the effects of valproic acid (VPA) have been studied using the same instrumental training tasks. VPA-treated rats displayed a severe deficit in acquiring a tone-signaled avoidance response. This deficit was attenuated in animals that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, few studies have found opposite evidence where VPA behaves as an inhibitor of cell proliferation. In one mice study, VPA treatment decreased hippocampal neurogenesis and produced cognitive decline and impairment in spatial memory test [ 131 ]. On this matter, Welbalt et al [ 132 ] demonstrated that fluoxetine prevents memory deficits and reduction in hippocampal cell proliferation caused by VPA.…”
Section: Pharmacological Treatments and Ahn In Animal Models And Humansmentioning
confidence: 99%
“…However, few studies have found opposite evidence where VPA behaves as an inhibitor of cell proliferation. In one mice study, VPA treatment decreased hippocampal neurogenesis and produced cognitive decline and impairment in spatial memory test [ 131 ]. On this matter, Welbalt et al [ 132 ] demonstrated that fluoxetine prevents memory deficits and reduction in hippocampal cell proliferation caused by VPA.…”
Section: Pharmacological Treatments and Ahn In Animal Models And Humansmentioning
confidence: 99%